2016
DOI: 10.1177/1541931213601067
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Individual Differences in Switching Performance and Task Engagement

Abstract: Strategic task switching is demanded in many real-world situations where effective simultaneous performance of concurrent tasks is not possible. Building from a model of strategic task overload management, the current study explored the influence of task load on the relationship between an individual’s task switching capability and task engagement. Only when high workload was present in both tasks was there a correlation between the capability to switch and subsequent action within tasks. In contrast, no relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The results showed that task-switching behavior has no significant effect on comprehension ability, but it significantly affects the fatigue and workload of the subjects. Clegg et al explored the effect of task load on the relationship between individual task-switching ability and task engagement 10 . The results showed that the correlation between switching ability and subsequent operation time was only found when there was a high workload in both tasks.…”
Section: Backgroundsmentioning
confidence: 99%
“…The results showed that task-switching behavior has no significant effect on comprehension ability, but it significantly affects the fatigue and workload of the subjects. Clegg et al explored the effect of task load on the relationship between individual task-switching ability and task engagement 10 . The results showed that the correlation between switching ability and subsequent operation time was only found when there was a high workload in both tasks.…”
Section: Backgroundsmentioning
confidence: 99%